Magnitude and determinants of intimate partner controlling behavior among women in sub-Saharan African countries from the recent demographic and health survey data: a multilevel analysis - Fantahun Andualem; Girum Nakie; Gidey Rtbey; Mamaru Melkam; Techilo Tinsae; Getasew Kibralew; Berihun Agegn Mengistie; Gebresilassie Tadesse; Getachew Muluye Gedef; Setegn Fentahun (BMC Public Health)
Abstract Background Intimate Partner Violence (IPV) is a major public health issue affecting physical, mental, and social well-being, particularly among women. In sub-Saharan Africa (SSA), IPV is widespread, with controlling behaviors being a common form. These behaviors include monitoring movements, social isolation, financial restrictions, and dictating daily choices. Data from Demographic and Health Surveys (DHS) highlight significant variations in these behaviors across countries and communities. Understanding the determinants of intimate partner controlling behavior (IPCB) requires a multi-level approach, considering individual, relational, community, and societal factors. IPCB has far-reaching consequences, impacting victims, families, and communities. This study aims to assess the magnitude and determinants of IPCB among reproductive-age women in SSA. Methods This study is a secondary data analysis based on the DHS conducted in eight Sub-Saharan African countries between 2021 and 2024. The study utilized the women’s data-women recode component (IR file) from the most recent DHS 8 datasets with the final weighted sample size 45,839 women. Multilevel logistic regression was conducted to assess factors associated with IPCB. All variables with a p-value < 0.05 were considered statistically significant. Results The prevalence of IPCB among reproductive age women in 8 sub-Saharan African countries was 54.47%, with a 95% CI of 54.02–54.93%. This study identified variables of age, marital status; education level, employment status, reproductive health factors, smoking habits, asset ownership, wealth index, residence, and mass media exposure were significantly associated with IPCB. Conclusion This study highlights a high prevalence of IPCB among reproductive-age women in eight Sub-Saharan African countries, with over half of the women reporting experiences of partner control. These findings suggest the presence of persistent gender power imbalances and socio-cultural norms that may contribute to male dominance in intimate relationships. These associations underscore the importance of promoting women’s autonomy and addressing structural gender inequalities. Programs and policies aimed at enhancing women’s access to education, economic resources, and information may contribute to reducing IPCB. Community-level interventions that challenge harmful socio-cultural norms and raise awareness through media campaigns could also be beneficial.